Aura alam : tumbuhan hutan paya laut tapak ramsar Negeri Johor - 514216 Abu Bakar Mohamed Salleh; Mohd. Nasir Husin; Mohd Faiz Azman 578957; Norwati Abd. Wahab, editor; Perbadanan Taman Negara Johor 578960 (Johor : Perbadanan Taman Negara Johor, 2011)
PRZSL